Studi Pemanfaatan Jenis Tumbuhan Obat Tradisional di Desa Nuku Kecamatan Oba Selatan, Kota Tidore Kepulauan - Raoda S Hukum; Abdur Kadir Kamaluddin; Mahdi Tamrin (Jurnal Forest Island, 2023)
Medicinal plants are one of the important components in medicine, which is a traditional herb and has been used since hundreds of years ago. Knowledge of the use of medicinal plants is obtained for generations and traditional knowledge if not written, over time will disappear. The use of plants as medicine continues to grow and increase with research related to the identification and utilization of plants that have the potential as medicine in traditional medicine. The purpose of this study is to identify the types of plants used as traditional medicine, identify the parts of plants used as traditional medicine, and identify the way of utilization of plant parts that are used as traditional medicine by the people of Nuku Village, South Oba District of Tidore Islands. The study was conducted in November 2021. This study is a derifrift study using observation and interview methods. The results of the study found the type of medicinal plants used by the community in Nuku Village of South Oba Subdistrict, Tidore Kepulaun City as a traditional medicine amounted to 29 types but only 25 types were identified. How to use medicinal plants by the Nuku community is by boiling, pounding, soaked. The most widely used way is to be pounded and boiled.